Economic Impacts of the Florida Citrus Industry in 2007–08 - Mohammad Rahmani; Alan W. Hodges (EDIS)
FE802, a 15-page paper by Mohannad Rahmani and Alan W. Hodges, presents estimates of the total economic impacts of the Florida citrus industry on the state economy based on production values for the 2007–08 production season. Includes references. Published by the UF Department of Food and Resource Economics, July 2009.